A Ritz type solution with exponential trial functions for laminated composite beams based on the modified couple stress theory. (1st May 2018) - Nguyen, Ngoc-Duong; Nguyen, Trung-Kien; Thai, Huu-Tai; Vo, Thuc P.
Abstract: This paper proposes novel Ritz functions for the size-dependent analysis of micro laminated composite beams with arbitrary lay-ups. Displacement field is based on a higher-order deformation beam theory and size effect is captured by the modified couple stress theory. Lagrange's equations are used to obtain the governing equations of motion. The present beam model, which can recover the classical one by neglecting the material length scale parameter, is used to predict the size-dependent responses of micro composite beams. The results indicate that the present study is efficient for bending, vibration and buckling problems of micro composite beams. Some new results are given to serve as benchmarks for future studies.